Enabling Innovative Governance: Ethical Leadership and Dynamic Capabilities in Government Digital Transformation - Xiangyu Bian; Bin Wang (Business Ethics and Leadership)
As governments face unprecedented technological disruption, understanding the enablers of administrative innovation becomes crucial. This study examines how ethical leadership fosters innovative behavior within government institutions across China’s western region, focusing on the interplay between leadership styles and dynamic capabilities. Data were collected through a survey targeting government officials in this region, employing a convenience sampling method. Over two months, two rounds of data collection were conducted, yielding 430 valid responses. Structural equation modeling was employed to analyze the data and test the hypotheses. The analysis reveals that ethical leadership not only directly promotes innovative behavior but also indirectly stimulates innovation by enhancing public service motivation ‒ a psychological mechanism that channels civil servants' intrinsic drive toward creative problem-solving. Moreover, the study identifies knowledge management capability, a specific dynamic capability, as a critical moderating factor. Organizations with higher levels of knowledge management capability exhibit stronger positive effects of ethical leadership on innovation, suggesting that robust digital and intelligent infrastructures amplify the leadership’s impact. By exploring these complex dynamics, the findings provide actionable insights for advancing public sector innovation, emphasizing the importance of ethical leadership and organizational readiness in navigating digital transformation.